2015
DOI: 10.22158/selt.v3n3p215
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teaching Collocations on the Students’ Perceptions toward Language Learning

Abstract: <p><em>Knowledge of collocation is fundamental for both receptive and productive use of the language. Collocation is often</em><em> </em><em>regarded as insurmountable obstacle to the attainment of native-like fluency. In other words, collocation skill has often been used to differentiate native and non-native speakers. The aim of this study is to investigate the effect of teaching collocation on the students’ attitudes toward language learning in the classroom. To enhance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Learners' perceptions in relation to the importance of teaching and learning collocations have also been reported in the literature. In this respect, Wu (2015) investigated the effect that teaching collocations has on the perceptions of elementarylevel EFL students. Overall, findings showed that most participants reported positive attitudes toward the explicit teaching of collocations in the classroom.…”
Section: Vial N_19 -2022mentioning
confidence: 99%
“…Learners' perceptions in relation to the importance of teaching and learning collocations have also been reported in the literature. In this respect, Wu (2015) investigated the effect that teaching collocations has on the perceptions of elementarylevel EFL students. Overall, findings showed that most participants reported positive attitudes toward the explicit teaching of collocations in the classroom.…”
Section: Vial N_19 -2022mentioning
confidence: 99%
“…Also, Wu (2015) studied the the effect of teaching collocation on the students' attitudes toward language learning in the classroom. To enhance both oral reading and speaking fluency, the researcher used the repeated reading method to check the participants' productive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have explored teachers' and students' perceptions on vocabulary teaching and learning are limited (Borg, 2006;Gao & Ma, 2011), while perception-based studies on collocations and collocation learning are scarce (Phuong, 2012;Wu, 2015). However, such investigation is important, as it would help identify mismatches between teacher and student perspectives, which then can be used to equip teachers with appropriate professional knowledge and beliefs to support students' learning efforts (Gao & Ma, 2011).…”
Section: Research On English Collocationsmentioning
confidence: 99%
“…Teachers also stated that they focused on commonly used collocations in activities such as comparing the synonyms of collocations, and they attributed students' collocational errors to the negative transfer from their native language, and students' habit of learning words in isolation. In Taiwan, Wu (2015) investigated the effects of using an online database on collocation teaching, and students' perceptions of collocations by means of a questionnaire, preand post-tests, and an interview. Students' answers showed that before training they lacked awareness of the concept of collocation, resulting in erroneous production of collocations.…”
Section: Research On English Collocationsmentioning
confidence: 99%